Precipitation Concentration in Highly Urbanized Regions — Case Study of Yangtze River Delta Urban Agglomeration - LIN Zequn; WANG Dayang; ZHANG Zhi; WANG Dagang (Renmin Zhujiang)
Amid global warming and enhanced human activities,precipitation has undergone significant changes in its intra-annual distribution,exerting a considerable impact on people's livelihoods and productivity,particularly in highly urbanized regions.This study focuses on the Yangtze River Delta urban agglomeration in China and utilizes multiple sources of precipitation data (including precipitation product data and meteorological station data) along with nighttime light data.The Gini Index (GI) is employed as an indicator of precipitation concentration. The Theil-Sen Median slope estimation and Mann-Kendall significance test are utilized for trend analysis,and a correlation analysis is employed to explore the relationship between urbanization levels and precipitation concentration.The results show that:① the root mean square error between the GI calculated from climate hazards Group infrared precipitation with station data (CHIRPS) and the station data results is 0.036,significantly lower than the results from CMFD data (0.067) and MSWEP data (0.083),which indicates that CHIRPS data demonstrates optimal applicability.② The unevenness of precipitation in the Yangtze River Delta urban agglomeration gradually increases from south to north,with a significant increasing trend in the central and western parts of the agglomeration.The intra-annual distribution of precipitation in the study area has become more concentrated,leading to an increased likelihood of extreme precipitation events.③ Urbanization is likely to promote the concentration of precipitation.The rapid development of cities enhances precipitation unevenness,especially in areas such as Nanjing,Wuxi,and Zhenjiang,making them more susceptible to urban flooding and related disasters.The findings of this research have practical implications for urban flood control design,urban road drainage system planning,and the development of emergency response plans for urban flood control.